1996
DOI: 10.1182/blood.v87.3.887.bloodjournal873887
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea increases hemoglobin F levels and improves the effectiveness of erythropoiesis in beta-thalassemia/hemoglobin E disease

Abstract: Hydroxyurea (HU) is one of several agents that have been shown to enhance hemoglobin (Hb) F levels in patients with sickle cell disease and may be useful as a therapy for beta-globinopathies. However, limited information exists on the effects of HU in patients with thalassemia. Accordingly, we examined the hematologic effects of orally administered HU in 13 patients with beta-thalassemia/Hb E, including four patients who had been splenectomized. These patients were treated with escalating doses (final range, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 24 publications
5
73
0
1
Order By: Relevance
“…The role of hydroxyurea and butyrate analogues is not established, although one Oakland patient has responded well to hydroxyurea and a study of 13 HbE/βthalassemics in Thailand showed a 10% Hb increase in hemoglobin. 13 HbE/β-thalassemia is the commonest form of severe thalassemia in the world and is most prevalent in the rapidly expanding and increasingly influential countries of Southeast Asia. It is also of growing importance in Europe, North America, and Australia, where the emphasis has traditionally been on Southern Europeans.…”
Section: Discussionmentioning
confidence: 99%
“…The role of hydroxyurea and butyrate analogues is not established, although one Oakland patient has responded well to hydroxyurea and a study of 13 HbE/βthalassemics in Thailand showed a 10% Hb increase in hemoglobin. 13 HbE/β-thalassemia is the commonest form of severe thalassemia in the world and is most prevalent in the rapidly expanding and increasingly influential countries of Southeast Asia. It is also of growing importance in Europe, North America, and Australia, where the emphasis has traditionally been on Southern Europeans.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic agents that stimulate fetal globin production, such as 5-azacytidine, decitabine, and hydroxyurea, all inhibit cell proliferation and cause cell growth arrest, which is known to promote irreversible apoptosis in cancer cells. [9][10][11][12][13][14][15][16][17] The chemotherapy agents are also mutagenic, a drawback for conditions requiring long-term treatment. 18,19 Several short-chain fatty acids (SCFAs) specifically induce transcription from the γ-globin gene promoter and in some patients can increase the efficiency of γ-globin mRNA translation.…”
Section: Introductionmentioning
confidence: 99%
“…6 Increases in hemoglobin concentration during hydroxyurea treatment have been described in a non-transfusion-dependent patient 7 and more recently in a transfusion-dependent patient 8 with homozygous β thalassemia, and in a series of patients with hemoglobin E/β thalassemia. 9 The butyrate compounds, derivatives of natural short-chain fatty acids, have offered potential therapy for Cooley's anemia following the observation that elevated plasma concentrations of α amino-n-butyric acid in infants of diabetic mothers delayed the normal switch from γ to β globin. 10,11 The observation that sodium phenylbutyrate, used for years as treatment for children with inherited urea-cycle disorders, 12 resulted in increased fetal hemoglobin production in K562 cells 13 led to early trials of this compound in patients with sickle cell disease 14 and Cooley's anemia.…”
mentioning
confidence: 99%